2005
DOI: 10.1111/j.0022-202x.2004.23556.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF -238 and -308 Promoter Polymorphisms with Psoriasis Vulgaris and Psoriatic Arthritis but not with Pustulosis Palmoplantaris

Abstract: Berger CL, Hanlon D, Kanada D, et al: The growth of cutaneous T-cell lymphoma is stimulated by immature dendritic cells. Blood 99:2929-2939, 2002 Braverman IM, Klein S, Grant A: Electron microscopic and immunolabeling studies of the lesional and normal skin of patients with mycosis fungoides treated by total body electron beam irradiation. J Am Acad Dermatol 16: 61-74, 1987

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 10 publications
4
48
1
Order By: Relevance
“…However, several population studies designed to evaluate the association between some TNF-a gene polymorphisms, such as G to A substitutions at positions À 238 and À 308, and PsA lead to conflicting results (Höhler et al, 1997;Hamamoto et al, 2000;Gonzalez et al, 2001Gonzalez et al, , 2002Hohler et al, 2002;Nishibu et al, 2002;Balding et al, 2003;Mossner et al, 2005;Rahman et al, 2006). In this study, we investigated the role of SNPs at positions À 238, À 308, and þ 489 within the TNF-a gene in PsA susceptibility, severity, and response to TNF-a inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several population studies designed to evaluate the association between some TNF-a gene polymorphisms, such as G to A substitutions at positions À 238 and À 308, and PsA lead to conflicting results (Höhler et al, 1997;Hamamoto et al, 2000;Gonzalez et al, 2001Gonzalez et al, , 2002Hohler et al, 2002;Nishibu et al, 2002;Balding et al, 2003;Mossner et al, 2005;Rahman et al, 2006). In this study, we investigated the role of SNPs at positions À 238, À 308, and þ 489 within the TNF-a gene in PsA susceptibility, severity, and response to TNF-a inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some authors found a strong association between these TNF-a promoter polymorphisms and PsA, suggesting that both polymorphisms could be used as biomarkers to predict the risk of the disease (Höhler et al, 1997;Hamamoto et al, 2000;Hohler et al, 2002;Nishibu et al, 2002;Balding et al, 2003;Mossner et al, 2005;Rahman et al, 2006). In particular, Hohler et al (2002) reported a highly significant association of the SNP À 238A with PsA in the German population and Balding et al (2003) observed the association of the SNP À 308 with PsA in Irish patients.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in the promoter of TNF, regulating its level, have been of interest for many years and some evidence has been provided for association with psoriasis. 87,88 However, the gene encoding TNF-a lies in the MHC region, and exhibits association with HLA class I alleles such as HLA-C. Hence, associations with TNF-a polymorphisms with psoriasis could be due to its proximity with HLA-C.…”
mentioning
confidence: 99%
“…An increased frequency of TNF-238A in psoriasis and PA was found in two studies in Western European white populations, 69,70 but was not confirmed in patients with PA in an English 71 and Estonian studies. 72 An investigation from Germany found a decrease in TNF-238A in AS, which was not seen in other studies: in Kaijzel et al 73 and Gonzalez et al studies, the frequency of TNF-238A was significantly decreased only with respect to healthy subjects HLA-B27 negative and to patients with AS HLA-B27 negative, respectively. In addition, a Dutch study found no difference in the transcriptional activity of the TNF-238A variant in RA population.…”
Section: G Ferraccioli Et Almentioning
confidence: 81%